Spatiotemporal dynamics of 53BP1 dimer recruitment to a DNA double strand break - Jieqiong Lou (Nature Portfolio, 2020)
53BP1 is a crucial factor involved in double strand break repair which blocks DNA end resection affecting DNA repair pathway choice. Here the authors reveal by live cell nuclear architecture analysis the spatiotemporal dynamics of 53BP1 oligomerization during a DSB DNA damage response.